Peningkatan Keterampilan Sosial dan Hasil Belajar menggunakan Model Pembelajaran Kooperatif Roundtable dan Carousel Feedback - Erita Febri Lestari; Mohammad Zainuddin; Budi Eko Soetjipto (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2019)
Abstract: This study aims to analyze the improvement of social skills and social studies learning outcomes of student using RoundTable and Carousel Feedback cooperative learning models. The method used classroom action research. The subjects of this study were fourth class students which amounted to 33 students at SD Negeri 3 Besuki. The result of this study obtained from observation, documentation, questionnaires, tests, and interviews. The results showed that RoundTable and Carousel Feedback cooperative learning models can improve social skills and social studies of student learning outcomes.Abstrak: Penelitian ini bertujuan menganalisis peningkatan keterampilan sosial dan hasil belajar IPS siswa menggunakan model pembelajaran kooperatif RoundTable dan Carousel Feedback. Metode penelitian ini merupakan penelitian tindakan kelas. Subjek penelitian yaitu siswa kelas IV.1 yang terdiri dari 33 siswa di SD Negeri 3 Besuki. Data hasil penelitian diperoleh dari observasi, dokumentasi, angket, tes, dan wawancara. Hasil penelitian model pembelajaran kooperatif RouundTable dan Carousel Feedback dapat meningkatkan keterampilan sosial dan hasil belajar IPS siswa.